2001
DOI: 10.5326/15473317-37-3-269
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for screw migration after triple pelvic osteotomy

Abstract: The objective of this retrospective study was to identify risk factors for screw migration after triple pelvic osteotomy (TPO) in clinical patients. The medical records, radiographs made immediately after surgery, and follow-up radiographs documenting a healed osteotomy were reviewed for 52 dogs treated with unilateral TPO and 38 dogs treated with bilateral TPO. Signalment, surgeon expertise, length of surgery, sequence of surgery in dogs treated bilaterally, use of ischial or ilial wires or both, screw depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
3
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 0 publications
5
60
3
2
Order By: Relevance
“…O uso de dois parafusos longos para a estabilização da osteotomia do ílio na OPT penetrando profundamente no sacro e não adentrando a canal medular, minimiza o afrouxamento dos mesmos (Simmons et al 2001). A colocação erroneamente ventral ao sacro pode resultar em lesão do nervo isquiático (Whelan et al 2004).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…O uso de dois parafusos longos para a estabilização da osteotomia do ílio na OPT penetrando profundamente no sacro e não adentrando a canal medular, minimiza o afrouxamento dos mesmos (Simmons et al 2001). A colocação erroneamente ventral ao sacro pode resultar em lesão do nervo isquiático (Whelan et al 2004).…”
Section: Resultsunclassified
“…O aumento na profundidade dos parafusos dentro do sacro no aspecto cranial da osteotomia ilial, juntamente com a cerclagem na osteotomia isquial, ajudam a evitar a migração dos parafusos (Simmons et al 2001).…”
Section: Introductionunclassified
“…While Simmons et al (2001), have reported that using a hemicerclage wire to secure ischial osteotomy decreases the frequency of screw migration, Remedios and Fries (1993) reported that, application of cerclage wire to the ischii and ilium osteotomy lines did not have any effect on screw loosening. In the screw loosening that occurred in our cases, we think that excessive movement of the animals played an important role and that rather than applying cerclage wire to the ischii, confinement of the patients to a restricted area for at least 20 days would combat this problem to a certain degree.…”
Section: Discussionmentioning
confidence: 99%
“…Complications reported for TPO surgery include diarrhea, bloody feces, hematuria, incision discharge, scrotal swelling and sciatic nerve paralysis 6,12,22 . Altunatmaz et al 12 reported that paralysis of sciatic nerve was observed in 3 cases and a collection occurred at the ischii osteotomy In 1 case of 22 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Following TPO in dogs, the most frequently complications are observed pelvic canal narrowing and screw loosening 6,[22][23][24][25][26] . Screw loosening being encountered in 33-36% of cases 22 .…”
Section: Discussionmentioning
confidence: 99%